ChemInform Abstract: Synthesis of β‐Amino Alcohols Using the Tandem Reduction and Ring‐Opening Reaction of Nitroarenes and Epoxides. Issue 43 (7th October 2016) - Shi, Chongyang; Ren, Cheng; Zhang, Erlei; Jin, Huile; Yu, Xiaochun; Wang, Shun
Abstract: The efficient procedure allows a mild access to various target compounds with a wide range of functionalities.